2002
DOI: 10.1046/j.1365-2362.2002.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher antioxidant defences in plasma and low density lipoproteins from rugby players

Abstract: Given that intermediate density and low density lipoproteins represent the most atherogenic fraction, this finding, in combination with the improved lipid and antioxidant status, would add to the link between regular physical activity and protection against cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 47 publications
6
37
0
3
Order By: Relevance
“…The results showed that athletes and non-athletes did not differ significantly in levels of investigated prooxidants (O 2 •-, H 2 O 2 , • NO, TBARS), but athletes had significantly higher levels of SOD and lower level of CAT activity. Higher SOD activity in athletes was also found in other studies, including studies involving karate athletes (Naghizadeh et al, 2009) soccer players (Briites et al, 1999;Cazzola et al, 2003), rugby players (Evelson et al, 2002;), jump-trained subjects (Ortenblad et al, 1997) and students of Physical Education and Sports Sciences (Balakrishnan & Anuradh, 1998). Regarding CAT activity, there is a number of previous studies that also found that it's acitivity is decreased in athletes compared with controls, but there are also a number of studies that reported no change in CAT activity as a consequence of exercise training (Miyazaki et al, 2001;Lekhi et al, 2007;Metin et al, 2003;Ortenblad et al, 1997;Balakrishnan & Anuradh, 1998).…”
Section: Assessment Of the Redox State Of Athletes And Non-athletessupporting
confidence: 67%
See 3 more Smart Citations
“…The results showed that athletes and non-athletes did not differ significantly in levels of investigated prooxidants (O 2 •-, H 2 O 2 , • NO, TBARS), but athletes had significantly higher levels of SOD and lower level of CAT activity. Higher SOD activity in athletes was also found in other studies, including studies involving karate athletes (Naghizadeh et al, 2009) soccer players (Briites et al, 1999;Cazzola et al, 2003), rugby players (Evelson et al, 2002;), jump-trained subjects (Ortenblad et al, 1997) and students of Physical Education and Sports Sciences (Balakrishnan & Anuradh, 1998). Regarding CAT activity, there is a number of previous studies that also found that it's acitivity is decreased in athletes compared with controls, but there are also a number of studies that reported no change in CAT activity as a consequence of exercise training (Miyazaki et al, 2001;Lekhi et al, 2007;Metin et al, 2003;Ortenblad et al, 1997;Balakrishnan & Anuradh, 1998).…”
Section: Assessment Of the Redox State Of Athletes And Non-athletessupporting
confidence: 67%
“…According to some studies, anaerobically trained subjects have a better antioxidant enzyme activity in blood, in tissues and especially in working muscle (Evelson et al, 2002;Marzatiko et al, 1997;(Radak et al, 2008b). It was also shown that a controlled protocol of endurance training is followed by an increase in antioxidant enzyme activity in plasma and other tissues (Tanskanen et al, 2010;Selamoglu et al, 2000;Lekhi et al, 2007).…”
Section: Assessment Of the Redox State Of Athletes And Non-athletesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finaud et al 15 stressed that oxidative stress and antioxidant capacity can be modified by magnitude of training loads in team sport such as rugby. Evelson et al 16 determined that resting SOD activity in well-trained rugby players was higher compared with sedentary men. In the present study, SOD activity was alike in the groups of sedentary individuals with tetraplegia and wheelchair rugby players with tetraplegia but was lower (approximately 20%) in the group of able-bodied rugby players compared with sedentary persons.…”
Section: Discussionmentioning
confidence: 99%